Career awareness, skills and acceptance of multimedia in teaching and learning, Malaysia: an expansion of the UTAUT model / Ting Siew King and Lai Tze Wee - Ting, Siew King; Lai, Tze Wee (UiTM Press, 2023)
Various information communication and technology (ICT) are used in teaching, learning and research collaborations in the higher learning institutions for the human capital development. Using the extended Unified Theory of Acceptance and Use of Technology (UTAUT) model, this paper aims to examine the determinants of the acceptance on the use of multimedia in learning among graduates who took economics related subjects in UiTM Cawangan Sarawak. The data was analysed using Partial Least Square (PLS) and Structural Equation Modelling (SEM). Our results show that out of five constructs, the new variable, namely career awareness, had the largest effect on the behavioural intention of using multimedia in learning among students. The moderating variables such as gender and age did not have any influence, while hard skills and soft skills had influence on the behavior of students. Several policies are recommended to further improve the determinants of the acceptance on the use of multimedia in the higher learning institutions.